The Unity of Phenomena on Different Scales as Exemplified by the Research of Albert Einstein and Paul Dirac: The Relevance of a New Universal Constant - Lieber, Michael (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
Reviewing the older, different approaches in physics may enable one to integrate them. This may provide new insights into physical existence. The theoretical approaches of Albert Einstein and Paul Dirac, during the earlier part of the twentieth century, indicate remarkable similarities, even though though their approaches respectively addressed different levels of existence, with seemingly different structures. Because of such similarity or unity, both theories or approaches predicted the positively charged electron. Having the same predictions experimentally confirmed in 1932, validating the two theories, both theories would have been common avenues to revealing a deeper feature of reality, universally present and marked by a new universal constant. It is unknown why both men did not see this and subsequently collaborate on elaborating such a unification and its implications. A new generation of physicists and philosophers, with new perspectives, my be able to do so.